THE EFFECT OF DOLLAR EXCHANGE RATE, GROSS DOMESTIC PRODUCT (GDP) AND CREDIT INTEREST RATES ON INDONESIAN FURNITURE EXPORT VOLUME - Ni Gede Ayu Puspita Dewi; Ni Ketut Budiningsih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
International trade occurs in all countries to increase the economic growth of a country including Indonesia. Indonesia's largest exports are in the non-oil and gas sector, especially the processing industry. One of the exports that utilizes natural resources to be processed and then traded is the furniture industry export, although the total furniture exports are not higher than other processing industry sectors, the furniture industry has great potential in the future. Furniture exports are one of the important sectors in the Indonesian economy, which contributes significantly to state revenue and job creation. The purpose of this study is toTo analyze the influence of the Dollar exchange rate, GDP and Credit Interest Rates in the long term and short term on the volume of furniture exports in Indonesia. This study uses quantitative data with a time span of 30 years, namely from 1994-2023 using the Error Correction Model (ECM) analysis method. The results of this study indicate that the Dollar exchange rate variable in the long term has a positive and significant effect on the volume of furniture exports in Indonesia, while in the short term it has a positive and insignificant effect on the volume of furniture exports in Indonesia. The GDP variable in the long term has a negative and significant effect on the volume of furniture exports in Indonesia, while in the short term it has a positive and significant effect on the volume of furniture exports in Indonesia. The Credit Interest Rate variable in the long term and short term has a negative and significant effect on the volume of furniture exports in Indonesia.